The impact of training of extension officers on poverty alleviation agricultural projects in Lepelle-Nkumpi Local Municipality of Capricorn District Municipality in Limpopo Province, South Africa - Mononyane, Kgaogelo Rebecca (My University, 2011)
The aim this study was to assess the impact of training of Extension Officers on poverty alleviation agricultural projects in Lepelle-Nkumpi Municipality. It aimed to assess if the skills that the Extension Officers acquired from the training offered to them did have a positive impact on the farmers and their projects. The objectives of the study thus, were: to identify and describe the nature and relevance of the training programs offered to the Extension Officers; to assess the impact of training and development on service delivery; and to suggest appropriate actions or interventions as may be necessary to improve the impact on service delivery. The study was qualitative in design and it sampled 10 projects. Data was gathered from Extension Officers attached to the 10 projects, famers, key informants consisting of community leaders and headmen and Deputy Managers. The study used focus group discussions, semi-structured interviews and a questionnaire to collect data. The key findings from this study are: computer literacy skills training seems to be the most popular one among the Extensions Officers. Some of them have never been given the opportunity to attend agricultural-related training. The study recommends that the computer literacy should be combined with the technical agricultural subjects so that the Extension Officers could be equipped with more information which will assist them to search for information from the internet and to impart the agricultural information to the farmers so that they could improve their productivity and income. Training in marketing and financial management is imperative for farmers to enhance their productivity and to manage their finances. The study also found out that the Extension Officers are not receiving adequate posttraining supervision in the form of evaluation. The frequent project visits and supervision of the extension officers’ daily duties by their superiors can improve their commitments to their work as well as increase the farmers’ productivity. Farmers lament the fact that they are offered the training theoretically and none of the extension officers make an effort to demonstrate to them practically. The work-related training which the Extension Officers have attended have improved service delivery at their work place because some of the beneficiaries since they started working in their projects, they have been getting their salary every month and their secret is that they cultivate the correct vegetables at the right time and this helps them to manage the three months waiting period easily. The Limpopo Provincial Department of Agriculture should extend the number of the extension officers in their municipality so that they could be available when they need them. The study adds to the knowledge base on the impact of training of extension officers on poverty alleviation agricultural projects.
Thesis (M.Dev.) --University of Limpopo, 2011
Keywords: Extension officers, training of; Poverty alleviation projects; farming; Agricultural projects; 630.92; Agricultural development projects; Economic development projects